Tumor mutational burden predicts neoantigen profiles and immunotherapy response in microsatellite stable tumors across different cancer types - Kondrateva, Olesia; Sonay, Tugce Bilgin; Zlobec, Inti; Anisimova, Maria (Frontiers in Immunology, 2026)
IntroductionImmunotherapy has shown positive response in many patients with microsatellite instable (MSI-H) tumors, but its effectiveness in microsatellite stable (MSS) tumors remains limited. We hypothesize that tumor mutational burden (TMB) can help identify a biologically distinct subset of MSS tumors that can benefit from immunotherapy.MethodsWe analyzed the molecular characteristics, including mutational landscape, mutational signatures, immune cell profiles and neoantigen load of MSS tumors with high TMB using data from colorectal cancer datasets (TCGA-COAD and TCGA-READ). After that, we extended these findings across other cancer types with MSI classification, further supporting the potential of using TMB as a biomarker for predicting immunotherapy response in MSS tumors.ResultsOur results show that MSS tumors with TMB greater than 50 mutations per megabase have POLE gene mutations, which lead to hypermutation. These hypermutated tumors show immune cell signatures that are more similar to MSI-H tumors, rather than MSS tumors with low TMB. We also found that MSS tumors with high TMB have a substantially higher number of neoantigens compared to low-TMB MSS tumors, suggesting they may respond better to immunotherapy, including a high proportion of predicted high-affinity neoantigens.DiscussionThese findings support the clinical relevance of TMB as a biomarker for neoantigen prediction and immunotherapy-relevant features in MSS tumors.